Quality of sleep and associated factors among medical interns in public universities in North Ethiopia - Meles, Dawit Afewerki; Ayele, Ashenafi Damte; Tsegaberhan, Hagos; Mossie, Tilahun Belete (Frontiers in Psychiatry, 2025)
ObjectiveTo assess the quality of sleep and associated factors among medical interns at public universities in North Ethiopia.MethodsWe conducted a cross-sectional study among 259 medical interns using a structured, interviewer-administered questionnaire. We employed the Pittsburgh Sleep Quality Index (PSQI) to determine the quality of sleep.ResultsOf the subjects, 72.6% were screened as having poor sleep quality. Anxiety [adjusted odds ratio (AOR) = 4.5, 95% CI: 1.93, 11.50; p < 0.001], poor sleep hygiene (AOR = 4.5, 95% CI: 1.4, 11.65; p < 0.001), current alcohol use (AOR = 3.85, 95% CI: 2.16, 6.89; p < 0.001), and current tobacco use (AOR = 2.4, 95% CI: 2.3, 25; p = 0.001) were significantly associated with poor quality of sleep.ConclusionPoor quality of sleep is prevalent among medical interns. Addressing anxiety, and alcohol and tobacco use and enhancing the practice of sleep hygiene among medical interns requires significant attention.